Perlindungan Konsumen Terhadap Pemberian Label Informasi Nilai Gizi Yang Tidak Sesuai - Adhyasta Dwi Pangestu; Siti Hapsah Isfardiyana (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This thesis aims to determine the form of legal protection for consumers regarding the right to information that should be obtained or obtained by consumers for violations committed by using nutritional value information labels (nutrition facts) that are not in accordance with the quality of food products. This research uses normative research, which focuses on examining the application of positive legal norms. The approaches used in this research are the statutory approach, the conceptual approach, and the case approach. The results of this research show that business actors still do not pay attention and there is a mismatch regarding the right to information and reality. Business actors who do not provide clear and correct information to consumers regarding the content contained in the food they produce cause business actors to violate the provisions in Article 4 of the Consumer Protection Law. Consumers who feel disadvantaged by business actors due to the content on the label not being in accordance with the quality of the product, the business actor can be held responsible based on Article 1365 of the Civil Code, Article 62 of the Consumer Protection Law, Article 97 of Law Number 18 of 2012 concerning food, and Government Regulation Number 69 of 1999 concerning Food Labels and Advertisements. Business actors as stated in Article 19 of Law Number 8 of 1999 concerning Consumer Protection are responsible for providing compensation for damage, pollution and/or losses to consumers resulting from consuming goods produced or traded in the form of refunds or replacement of goods of the same or equivalent value. In the event that consumers feel disadvantaged, they can take legal action in accordance with dispute resolution through court or outside court.